(3GdeYJeO aj CUhd Gdabgs - (3CHh GdbGSe Hf CMeO Hf Ydj Hf EHQGgje GdRjGfj , J (B1249 (3g`s
(3ChdgG (B:s
(3hMci GdTjN GHhYHOGddg Yf GdTjN CHj GdMSf Cf GdELeGY s
(3BNQgG (B:s
(3hgh GdUMjM dCf bhdge MLI ceG Cf bhd GdfHi Udi Gddg Ydjg MLI s
(3Vef eLehY , JQJjHgG (B: (3GdeLdO GdKGfis
(3HgG fXGe GdJYbjHIs
(3cJHJ GdfSNI HQSe NRGfI GdEeGe YHOGddg Hf MeRg Hf SdjeGfs
(3fSNI KGdKI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1732s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs